Retinopathy in patient with AC hemoglobinopathy - Aguiar,Aline Guerreiro (2020)
Abstract Hemoglobin C is the second most frequent Hb variant in Brazil and the world. Hemoglobin C trait is described as a benign and asymptomatic condition. There is little information in the literature about the association of retinal vascular disease and the presence of hemoglobin AC, being this information restricted to a few case reports. This case report describes a 26-year-old female patient with hemoglobin C trait. She presents areas of non-perfusion and arteriovenous shunts in the retinal temporal periphery of the left eye, like changes in Goldberg’s stage II of proliferative sickle retinopathy. After three years of follow-up, the patient exhibits the same the alteration in right eye as well.